What's the score? : 25 years of teaching women's sports history - Morris, Bonnie J., 1961- (Red Lightning Books, 2022)
"Who is the first female athlete you admired? Were male and female athletes treated differently in your high school? Is there a natural limit to women's athletic ability? How has Title IX opened up opportunities for women athletes? Every semester since 1996, Bonnie Morris has encouraged students to confront questions like these in one of the most provocative college courses in America: Athletics and Gender, A History of Women's Sports. What's the Score?, Morris's energetic teaching memoir, is a peek inside that class and features a decades-long dialogue with student athletes about the greater opportunities for women-on the playing field, as coaches, and in sports media. From corsets, to segregated schoolyards, to the WNBA, we find women athletes the world over conquering unique barriers to success. What's the Score? is not only an insider's look at sports education but also an engaging guide to turning points in women's sports history that everyone should know"--